2009
DOI: 10.4067/s0718-27912009000300006
|View full text |Cite
|
Sign up to set email alerts
|

EDAPHIC MESOFAUNA COMMUNITY STRUCTURE IN ORGANIC AND CONVENTIONAL MANAGEMENT OF CRANBERRY (Vaccinium sp.) PLANTATIONS: AN AGROECOLOGICAL APPROACH

Abstract: The aim of the present study was to determine and compare taxa richness, abundance and diversity of the edaphic mesofauna community between plantations of cranberries (Vaccinium sp.) subjected to organic and conventional management in farms in central-south Chile (37°28'S), as also to evaluate changes produced in their diversity and abundance diversity and abundance, as result of the change from conventional to organic management. In July 2006 two farms were chosen, one with one year under organic management (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
2
3
0
2
Order By: Relevance
“…It was also found that under organic agricultural management, the Mesofauna increases its abundance (Kautz et at., 2006;Peredo et al, 2009) possibly due to the specialization in the consumption of the sources of litter left by crops (Kautz et al, 2006; PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.710v1 | CC-BY 4.0 Open Access | rec: 17 Dec 2014, publ: 17 Dec 2014 PrePrints Milcu et al, 2006). The results presented here also support that assumption.…”
Section: Discussionsupporting
confidence: 80%
“…It was also found that under organic agricultural management, the Mesofauna increases its abundance (Kautz et at., 2006;Peredo et al, 2009) possibly due to the specialization in the consumption of the sources of litter left by crops (Kautz et al, 2006; PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.710v1 | CC-BY 4.0 Open Access | rec: 17 Dec 2014, publ: 17 Dec 2014 PrePrints Milcu et al, 2006). The results presented here also support that assumption.…”
Section: Discussionsupporting
confidence: 80%
“…It was also found that under organic agricultural management, the Mesofauna increases its abundance ( Kautz, Lopez-Fando & Ellmer, 2006 ; Peredo et al, 2009 ) possibly due to the specialization in the consumption of the sources of litter left by crops ( Kautz, Lopez-Fando & Ellmer, 2006 ; Milcu et al, 2006 ). The results presented here also support that assumption.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that under organic agricultural management, the Mesofauna increases its abundance (Kautz et at., 2006;Peredo et al, 2009) possibly due to the specialization in the consumption of the sources of litter left by crops (Kautz et al, 2006; PeerJ PrePrints | http://dx.doi.org/10.7287/peerj.preprints.710v1 | CC-BY 4.0 Open Access | rec: 17 Dec 2014, publ: 17 Dec 2014 Milcu et al, 2006). The results presented here also support that assumption.…”
Section: Discussionsupporting
confidence: 82%